FRI0255 Evaluation of early markers of cardiovascular risk in subjects affected by systemic rheumatic diseases. (23rd January 2014) - Lanciano, E.; Ciccone, M.M.; Zito, A.P.; Pinto, M.; Gesualdo, M.; Scicchitano, P.; Sassara, M.; Iannone, F.; Lapadula, G.
Abstract : Background: Our study investigates whether rheumatic autoimmune conditions are associated with an increased Carotid Intima-Media Thickness (C-IMT) when compared with healthy control subjects and evaluates possible discrepancies existing among the different rheumatic diseases types. Methods: A total of 108 patients, 15 males and 93 females, aged between 18 and 82 years (mean age 51±14 years), fulfilling the ACR criteria for SLE, APS, SSc, PM/DM, MCTD, SS attending the Rheumatology Unit at Univeristy of Bari – Policlinico, were recruited between November 2010 and March 2011. Patients were subdivided into the following two groups: 1) Group SSc (Sclerodermic patients): 60 patients, 7 males and 53 females, mean age 52±14 years; 2) Group NoSSc (Non-Sclerodermic patients): 48 patients, 8 males and 40 females, mean age 50±15 years. We also enrolled 108 healthy controls, matched by sex and age with patients. All patients underwent to structured interview, physical examination, laboratory evaluation and two-dimensional echo-color Doppler of the carotid arteries. Results: There were no significant differences between SSc and NoSSc regarding any of the demographics and traditional cardiovascular risk factors, except from total cholesterol that was significantly higher in SSc group, compared with the NoSSc group. The mean duration of disease since diagnosis was 8 (range 3 to 13) years, comparable in the two groups (a little longer in NoSSc ). Total cholesterol was significantly higher in SSc patients (mean value 224, range 196-252 mg/dL) than in NoSSc patients (mean value 203, range 194-212 mg/dL). HDL cholesterol value was slightly raised, if compared with a cut-off value of 45 (mean value 47, range 37-57 mg/dL), and was substantially similar in the two groups. Idem for LDL and triglycerids values that were a little raised in comparison with the cut-off values. The distribution of cardiovascular risk factors was similar in the two groups. We found a mean C-IMT value of 0.86 mm (range 0.73 to 0.99 mm) that resulted from the following values: 0.91±0.1 mm in SSc group, 0.80±0.14 in NoSSc group. The difference between groups was significant (p-value <0.05). We also evaluated C-IMT in control subjects, obtaining the following result: 0.83±0.13 mm. The percentage of carotid plaques in each group was 12% for SSc and 17% for NoSSc, with a mean value of 14%. Conclusions: We found no signs of increased atherosclerosis, as assessed by C-IMT measurement, among patients with rheumatic autoimmune diseases and healthy controls, and a strong evidence of higher risk in patients with SSc respect to patients with SLE, PM/DM, APS, MCTD and SS. Considering the current state of knowledge, the necessity of optimising prevention and treatment of CVD in patients with systemic rheumatic disease, in particular way those affected by SSc, must be emphasised. A comprehensive identification of cardiovascular risk profile in those diseases is an opportunity to improve prognosis of these patients, since most of the identified risk factors are susceptible of modification. Certainly, further researches are favourable in order to improve life duration and cardiovascular outcomes of these patients. Disclosure of Interest: None Declared